RESEARCH METHODS IN SPORT TRAINING - Duško Bjelica (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2010)
Objective knowledge, which is confirmed by social and economic development, is achieved only on the basis of scientific research growing out of systematic and analogous collection of established facts. Science that deals with the totality of all research forms and ways is called methodology. Technical methods of research are based on the organization of experiments and evaluation of data acquired by precise measuring. Logical methods are characterized by scientific data processing on the basis of which relevant conclusions are deducted. These conclusions themselves serve as the basis of further development of theories and systems. Sport, together with sport training, has its own adequate methodology. Sport methodology involves specific techniques and logical operations that can be applied only for typical occurrences on the field of sport training. Most frequent research methods in the field of sport training are: 1. Analytical method, which determines actual forces as causes. 2. Synthetic method, which determines certain tendencies as results. 3. Static method of research.